Hydrogen import pathway comparison framework incorporating cost and social preference: Case studies from Australia to Japan. (10th July 2017) - Chapman, Andrew J.; Fraser, Timothy; Itaoka, Kenshi
Summary: Recent proposals to produce and import hydrogen from Australia to Japan for electricity generation raise questions about how to compare the costs and feasibilities of different hydrogen import pathways. This paper establishes a framework for the comparison of technological, economic, and social costs and feasibility. The framework is then applied to 3 potential production and import case studies. First, a benchmark case study is considered which uses Australian brown coal from the Latrobe Valley combined with carbon capture and sequestration (CCS) technology. The second and third comparative case studies use renewable energy and electrolysis near port facilities in Karratha, Western Australia, using solar power exclusively as the renewable energy source, and Gladstone, Queensland, using a combination of onshore wind and solar‐based generation. The study finds that comparative pilot project generation costs for the brown coal pathway are between approximately 5.9 and 15.4 yen/kWh cheaper than for solar and/or wind‐based pathways. However, limitations of scaling up CCS, a limited brown coal supply, long‐term reducing costs of renewables, and the prospect to develop complementary renewable infrastructure make a strong counterargument for investment in solar and wind pathways as an alternative to brown coal and CCS. Abstract : Statement of Novelty This study provides a comparative framework for the evaluation of fossil fuel and renewable energy to hydrogen pathways. The framework analyses and compares geographic, techno‐economical, and social aspects of hydrogen pathways, providing an original, holistic decision‐making tool. A consideration of technical externalities and social preference provides a framework that incorporates previously overlooked aspects within policy and project decision making.